2019
DOI: 10.1186/s13104-019-4698-x
|View full text |Cite
|
Sign up to set email alerts
|

Development, validation and translation of cardiopulmonary resuscitation and automated external defibrillator training and placement bilingual questionnaire

Abstract: ObjectivesThis paper describes the development and translation of a questionnaire purported to measure (1) the perception of the placement strategy of automated external defibrillator, (2) the perception on the importance of bystander cardiopulmonary resuscitation and automated external defibrillator (3) the perception on the confidence and willingness to apply these two lifesaving interventions as well as (4) the fears and concerns in applying these two interventions. For construct validation, exploratory fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…For the construct validity testing, the KMO value for all seven constructs (perceptions, attitudes, perceived norms, self-efficacy, intentions, behaviours, barriers) and 44 items was 0.777. These findings are consistent with the findings of the original validation study by Chew et al [20], which was 0.79. This may be influenced by the use of a validated construct from the original study for perceptions (perception of AED placement strategies and perception of importance of CPR and AED), barriers (concerns of injuring victims during CPR and AED, and concerns of legality in performing CPR and AED), and behaviours (confidence and willingness to perform CPR and AED), even though different populations produce nearly identical results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the construct validity testing, the KMO value for all seven constructs (perceptions, attitudes, perceived norms, self-efficacy, intentions, behaviours, barriers) and 44 items was 0.777. These findings are consistent with the findings of the original validation study by Chew et al [20], which was 0.79. This may be influenced by the use of a validated construct from the original study for perceptions (perception of AED placement strategies and perception of importance of CPR and AED), barriers (concerns of injuring victims during CPR and AED, and concerns of legality in performing CPR and AED), and behaviours (confidence and willingness to perform CPR and AED), even though different populations produce nearly identical results.…”
Section: Discussionsupporting
confidence: 92%
“…The KMO value for this study was between 0.7 and 0.8, indicating a good correlation with each other, and factor analysis was appropriate for this dataset. The Bartlett test of sphericity values for all constructs was significant, which is line with the previous study indicating that there was appropriate correlation between the items based on the correlation matrix [20]. The communality values for all items had a value of >0.25 (0.296-0.853).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The reliability and validity were tested using four different methods: the factor loading, Cronbach’s alpha, composite reliability, and average variance extracted (AVE). According to Chew et al (2019), the values of the variables in factor loading found to be less than 0.7 should be avoided unless they are essential for validity contents. Thus, the threshold value was determined as 0.6.…”
Section: Discussionmentioning
confidence: 99%
“…All factor loadings and all AVEs were more than 0.6 and 0.5, respectively, as shown in Table 3. Chew et al (2019) indicated that values of the variables in factor loading that are less than 0.6 should be avoided, while values over 0.6 are acceptable. Four items (i.e.…”
Section: Discussionmentioning
confidence: 99%